Enantioselective transformation of fluoxetine in water and its ecotoxicological relevance. Issue 1 (December 2017) - Andrés-Costa, María; Proctor, Kathryn; Sabatini, Marco; Gee, Anthony; Lewis, Simon; Pico, Yolanda; Kasprzyk-Hordern, Barbara
Abstract European legislation focusing on water quality is expected to broaden to encompass several pharmaceuticals as priority hazardous substances. This manuscript aims to challenge current regulatory approaches that do not recognize stereochemistry of chiral pharmaceuticals by testing the hypothesis that environmental transformation and effects of chiral pharmaceuticals are stereoselective. Our experiments revealed that, while degradation of chiral fluoxetine (FL) in river water occurs via non-enantioselective photochemical and mildly-enantioselective microbial processes favoring the (R )-enantiomer, a pronounced enantioselectivity favoring (S )-FL (leading to the formation of (S )-NFL (norfluoxetine)) is observed during activated sludge treatment. Toxicity tests proved strong enantiomer-specific toxicity in the case ofTetrahymena thermophila, protozoa that are utilized during activated sludge treatment ((R )-FL is 30× more toxic than (S )-FL; (S )-NFL is 10× more toxic than (S )-FL). This is of paramount importance as preferential degradation of (S )-FL in activated sludge microcosms leads to the enrichment of FL with 30× more toxic (R )-FL and formation of 10× more toxic (S)-NFL. It is commonly assumed that a decreased concentration of FL leads to decreased biological impact. Our study proves that despite the overall decrease in FL concentration, accumulation of toxic (R )-FL and formation of toxic (S )-NFL leads to much higher than presumed toxicological effects.